Upaya Meningkatkan Hasil Belajar IPS Melalui Metode Mind Map dengan Media Powerpoint - Anisa Fatmawati (JSSH (Jurnal Sains Sosial dan Humaniora), 2017)
The low learning outcomes were caused by the lecture method, question and answer and discussion based on the students’ worksheet as well as the unoptimum media of teaching. The research was aimed to improve students’ learning outcome of social science on the topic of economic activities related to the natural resources in their areas through Mind Map method and Powerpoint media for the fourth graders SDN Pasir Wetan. This classroom action research consisted of two cycles and it had 2 meetings and each cycle. The procedure was planning, acting, observing and reflecting. The data were obtained through student’ worksheet (LKS), evaluation test (at the end of the cycle), scoring sheet of teacher activities, observation sheet of students’ activity in their cognitive, affective and psychomotor aspect and there were field notes and interview. The research and discussion that the use Mind Map methode and Powerpoint media could improve students’ cognitive aspect proven by mean of first cycle 72,57 (good criteria) and 71,65% level of achievement (good enough) while second cycle 80,31 (very good criteria) and 92,26% level of achievement (very good). The affevtive mean score showed 3,08 (good criteria) in the first cycle and the mean score 8,66 was in the second cycle (very good). The psychomotor aspect showed with mean score that 3,25 was in the first cycle (good criteria) and 3,4 was in the second cycle (very good). It could be drawn that Mind Map methode and Powerpoint media could improve students’ learning outcomes off social science for the fourth graders.